Evaluation of the EULAR/American College of Rheumatology Classification Criteria for Systemic Lupus Erythematosus in a Population‐Based Registry. Issue 5 (11th January 2023) - Guttmann, Allison; Denvir, Brendan; Aringer, Martin; Buyon, Jill P.; Belmont, H. Michael; Sahl, Sara; Salmon, Jane E.; Askanase, Anca; Bathon, Joan M.; Geraldino‐Pardilla, Laura; Ali, Yousaf; Ginzler, Ellen M.; et al.
Abstract : Objective: Using the Manhattan Lupus Surveillance Program, a multiracial/ethnic population‐based registry, we aimed to compare 3 commonly used classification criteria for systemic lupus erythematosus (SLE) to identify unique cases and determine the incidence and prevalence of SLE using the EULAR/American College of Rheumatology (ACR) criteria. Methods: SLE cases were defined as fulfilling the 1997 ACR, the Systemic Lupus International Collaborating Clinics (SLICC), or the EULAR/ACR classification criteria. We quantified the number of cases uniquely associated with each and the number fulfilling all 3 criteria. Prevalence and incidence using the EULAR/ACR classification criteria and associated 95% confidence intervals (95% CIs) were calculated. Results: A total of 1, 497 cases fulfilled at least 1 of the 3 classification criteria, with 1, 008 (67.3%) meeting all 3 classifications, 138 (9.2%) fulfilling only the SLICC criteria, 35 (2.3%) fulfilling only the 1997 ACR criteria, and 34 (2.3%) uniquely fulfilling the EULAR/ACR criteria. Patients solely satisfying the EULAR/ACR criteria had <4 manifestations. The majority classified only by the 1997 ACR criteria did not meet any of the defined immunologic criteria. Patients fulfilling only the SLICC criteria did so based on the presence of features unique to this system. Using the EULAR/ACR classification criteria, age‐adjusted overall prevalence and incidence rates of SLE in Manhattan were 59.6 (95% CI 55.9–63.4) and 4.9 (95% CI 4.3–5.5) per 100, 000 population, with age‐adjusted prevalence and incidence rates highest among non‐Hispanic Black female patients. Conclusion: Applying the 3 commonly used classification criteria to a population‐based registry identified patients with SLE fulfilling only 1 validated definition. The most recently developed EULAR/ACR classification criteria revealed prevalence and incidence estimates similar to those previously established for the ACR and SLICC classification schemes.